Cytotoxic Therapy of Colorectal Carcinoma in Pakistan - Anwar Ejaz Baig (ziauddin University, 2024)
Colorectal carcinoma (CRC) is associated with highest cancer mortality rate next to lung carcinoma. Cancer statistical report by WHO in Pakistan indicate that colorectal carcinoma is the predominant cause of cancer mortality ranking seventh in women and eighth in men. Colorectal cancer patients in Pakistan are presented with distinct clinical features e.g. subsided lesions, comparatively young age and rapidly progressive advanced cancer stage with multiple sites of distant metastases. These features substantially contribute to surgical complications and assign severity to the toxic profile of cancer chemotherapy. Early diagnosis of CRC, which is otherwise a slow developing cancer, reduces the aforementioned added complications with cancer treatment. Multiple factors like inappropriate and incorrect awareness, socioeconomic strain and inadequate health care facilities prevent early diagnosis of the disease. Screening for CRC is both complex and challenging in populations with economic instability and high incidence rate due to lack of factors like risk stratification, patient's acceptance, adequate financial insurance, appropriate diagnosis, treatment and follow up.